Sediment properties of gravity core DG12-GC02 obtained on the Drygalski Basin in the Ross Sea - Sangbeom Ha; Jae Il Lee; Young-Suk Bak; Kyu-Cheul Yoo; Boo-Keun Khim (PANGAEA, 2024)
The MS was measured at 1 cm interval using Bartington MS-2B susceptibility meter. The WC was also measured at 1 cm interval using 1 cm thick subsamples by calculating the following equation with an assumption of 35 psu for the salinity of seawater: WC (%) = (mass of wet sediment - (mass of dry sediment+mass of salt))/(mass of wet sediment exttimes 100). The grain size was measured at 4 cm intervals. After removing organic matter using 10% H2O2 and biogenic silica using 2N NaOH, the coarse fraction (>63 μm) was analyzed using 1 phi interval sieves. In contrast, the fine fraction (<63 μm) was analyzed using Micrometrics Sedigraph III 5120. The grain size classification followed the scheme of Folk and Ward (1957). The Total Carbon (TC) and Total Nitrogen (TN) contents were analyzed using an elemental analyzer (FLASH 2000 NC Analyzer) with an analytical precision of less than 0.1%. Total Inorganic Carbon (TIC) was measured using UIC CO2 coulometer (Model CM5240). CaCO3 concentration was calculated by multiplying TIC content by 8.333 (i.e., the ratio of CaCO3 and carbon). TOC content was calculated as the difference between TC and TIC contents. Biogenic silica concentration was measured at 8 cm intervals (GC01, GC04, and GC05) and 4 cm intervals (GC02) using the wet alkaline sequential extraction method using 1N NaOH solution at 85C modified from DeMaster (1981) at Pusan National University. Biogenic opal content was calculated by multiplying biogenic silica concentrations by 2.4 (i.e., the ratio of biogenic opal and Si) (Mortlock and Froelich, 1989). The analytical precision for the biogenic opal measurement was ±1%. The carbon isotope composition (δ13CSOM) of the sediment organic matter was measured for selected sediment samples at 10 cm intervals from GC01 and at 8 or 16 cm intervals from GC02, 04, and 05 using elemental analysis-isotope ratio mass spectrometry (EA-IRMS: Europa Scientific 20-20 isotope ratio mass spectrometer) at Iso-Analytical Ltd. (UK). The δ13CSOM values were expressed in conventional delta notation, which is the per mil deviation from the V-PDB standard. The analytical precision for δ13CSOM was approximately ±0.08 extperthousand.
In: Ha, S et al. (2024): Sediment properties, geochemical proxies, clay mineral composition and diatom assemblage of gravity cores obtained on the Drygalski Basin in the Ross Sea since Last Glacial Maximum [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.966442